On the existence of piecewise-continuous separatrix curves for a certain class of pulse systems - Svistun, O. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Sufficient conditions of existence of piecewise continuous separatrix curves are obtained for a certain class of systems of differential equations with pulse influence for small $ε ≥ 0$.